Effect of Bile Acid on Fetal Lung in Rat Model of Intrahepatic Cholestasis of Pregnancy - Ling Yu; Yiling Ding; Ting Huang; Xiaoxia Huang (International Journal of Endocrinology)
Objective. To determine the correlation between maternal bile acid (BA) level and fetal pulmonary surfactant in rats and study the effects of BA on fetal lung in rat model of intrahepatic cholestasis of pregnancy. Methods. Forty pregnant rats were treated with (A) 5.5 mg/kg BA, (B) 1.4 mg/kg BA, and (C) 1 ml physiological saline. Levels of total bile acid (TBA), ALT, AST, TBIL, DBIL, and SP-A were determined and the lungs of fetal rats were analyzed for pathological changes. Results. Groups A and B intervened with BA showed significant higher level of TBA in both maternal and fetal serum, more mortality rate of fetal rats, more concentration of SP-A in fetal serum, and wider alveolus mesenchyme of fetal rats than the control Group C. Higher level of BA associated with increased fetal risk and lower numerical density of mitochondria in type II alveolar epithelial cells. The levels of TBA in maternal serum were found to have significant positive correlation with those in fetal serum and SP-A level but negatively with the area of alveolus and the numerical density of lamellar body. Conclusions. The TBA level in maternal serum showed significant association with lung pathological changes in fetal rats.